Evolution of photoluminescence as a function of the structural order or disorder in CaMoO4 nanopowders - Marques, A. P. A. (2008)
CaMoO4 nanopowders were prepared by the complex polymerization method. The materials were characterized by x-ray diffraction (XRD) and by Fourier transform infrared, Raman, and optical reflectance spectroscopies. The data revealed the presence of crystalline scheelite-type phase CaMoO4 and the absence of additional phases. The surface morphology was monitored by hieh-resolution scanning electron microscopy (HR-SEM). The HR-SEM and XRD characterizations both revealed a tendency for the particle size to increase with rising treatment temperatures. The disordered nanopowders showed strong emission of photoluminescence, which dropped to minimal levels in the ordered nanopowders. These differences in the photoluminescence of disordered and ordered nanopowders were attributed to complex cluster vacancies. (C) 2008 American Institute of Physics.